Proceedings of the 2010 ACM Symposium on Applied Computing 2010
DOI: 10.1145/1774088.1774601
|View full text |Cite
|
Sign up to set email alerts
|

Cross-organizational process monitoring based on service choreographies

Abstract: Business process monitoring in the area of service oriented computing is typically performed using business activity monitoring technology in an intra-organizational setting. Due to outsourcing and the increasing need for companies to work together to meet their joint customer demands, there is a need for monitoring of business processes across organizational boundaries. Thereby, partners in a choreography have to exchange monitoring data, in order to enable process tracking and evaluation of process metrics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 10 publications
0
34
0
3
Order By: Relevance
“…The lack of a standardized monitoring API is a real problem here. Research has dealt with monitoring choreographies (Wetzstein et al, 2010;Lazovik et al, 2004;Roder et al, 2011), but very little research has been performed aimed specifically at BPMN. Another way to monitor a distributed environment is having a centralized system in place (e.g.…”
Section: Related Workmentioning
confidence: 99%
“…The lack of a standardized monitoring API is a real problem here. Research has dealt with monitoring choreographies (Wetzstein et al, 2010;Lazovik et al, 2004;Roder et al, 2011), but very little research has been performed aimed specifically at BPMN. Another way to monitor a distributed environment is having a centralized system in place (e.g.…”
Section: Related Workmentioning
confidence: 99%
“…To monitor the whole choreography, proposed solutions [20], [4], [14] consist of a central monitor which is notified by each participant whenever an event happens (e.g. using a publish/subscribe mechanism [14]). Nevertheless, this may present a single point of failure and not be adaptive when there is no common trusted party among all participants.…”
Section: External Flow Monitoringmentioning
confidence: 99%
“…The first one [13] uses a common audit format which allows processing and correlating events across different BPEL engines. The second approach [14] introduces complex event specification and uses a choreography instance identifier (ciid) to deal with event correlation (which is not supported in [13]). …”
Section: Implementation Guidelinesmentioning
confidence: 99%
“…While business process monitoring can be more easily achieved in a service orchestration context, where there is a centralized entity in charge of the synchronization of the component services (e.g., [9] for monitoring of BPEL processes), the monitoring of CBPs in a multiple organizational setting present additional challenges, because it may require that different participants interchange monitoring data. A recent research effort toward this direction can be found in [42], that proposes an event-based monitoring approach based on BPEL4Chor.…”
Section: Fig 1 Example Of Adaptation Policymentioning
confidence: 99%